MENGHARGAI MODUS-MODUS ESENSIAL MANUSIA SEBAGAI UPAYA MENGATASI PROBLEM DEHUMANISASI DI INDONESIA - Nugroho, Ellen Christiani (Faculty of Humanities, Diponegoro University, 2011)
The animality of man we can fairly grasp, but perplexities arise when we try to define the humanity of man. Contemporary, modern human knowledge tends to describe the essence of man as a kin of animal or a type of machine. Those descriptions elude the essential modes of man which are preciousness, uniqueness, opportunity, nonfinality, process and events, solitude and solidarity, reciprocity, and sanctity. Through further elaboration on the essence of humanity as a being between animality and divinity, in Heschelâ€™s concept of man we may find a remedy to dehumanization as the contemporary humanâ€™s plight and problems, especially as it emerges in our country as violent cases against humanity. Â Keywords: humanity, humanization, dehumanization, modern human, essential modes of man